Serum High-Density Lipoprotein-Cholesterol Concentration as Determinant of Poor Glycemic Control in Type 2 Diabetes Mellitus Patients at a Public Health Center in Jakarta, Indonesia - Yenny; Patricia Budihartanti Liman; Joice Viladelphia Kalumpiu; Triasti Khusfiani; Jihan Samira; Arleen Devita (Global Medical & Health Communication (GMHC), 2025)
The risk factors for glycemic control in type 2 diabetes mellitus (T2DM) are poorly understood. This study assessed the prevalence of poor glycemic control and the predictive factors of poor glycemic control among T2DM outpatients in the community. This 30-day community-based cross-sectional study was conducted among ambulatory T2DM patients in Jakarta from May to June 2023. Data on age, sex, and level of education were collected by questionnaire, whereas data on body mass index, lipid profile, and HbA1c were obtained by measurement. Glycemic control was good if HbA1c <7 % and poor if HbA1c≥7%. The relationships between age, sex, level of education, body mass index, lipid profile, and glycemic control were determined using simple logistic regression. Multivariable logistic regression was used to determine the most influential risk factors of glycemic control. Poor glycemic control was found in 68.4% respondents, and obesity in 57.9% of respondents. After adjustment for age, level of education, and triglyceride concentration, the most influential factor for glycemic control was HDL concentration (aOR=4.43, 95% CI=1.19–16.5, p=0.027). Patients with T2DM with HDL <40 mg/dl had a 4.63 times significantly higher odds of poor glycemic control than those with HDL ≥40 mg/dl. This study found a high prevalence of poor glycemic control in the community setting among individuals with T2DM, with HDL concentration as the most significant predictor. Meanwhile, a triglyceride concentration of ≥150 mg/dl independently provided 58% greater protection against glycemic control (p=0.035), but the effect was not significant after adjustment (p>0.05). The high prevalence of poor glycemic control, dyslipidemia, and obesity in T2DM patients requires routine screening and monitoring accompanied by health education on lifestyle modification for risk factor control, thus minimizing the risk of complications.